ARC: An Open Web-Platform for Request/Supply Matching for a Prioritized and Controlled COVID-19 Response - Courcol, Jean-Denis; Invernizzi, Cédric F.; Landry, Zachary C.; Minisini, Mikhaél; Baumgartner, Dieter A.; Bonhoeffer, Sebastian; Chabriw, Barbara; Clerc, Estelle E.; Daniels, Michael; Getta, Pavlo; Girod, Matthieu; Kazala, Kinga; et al. (Frontiers in Public Health, 2021)
n 2020 the world was hit by the COVID-19 pandemic putting entire governments and civil societies in crisis mode. Around the globe unprecedented shortages of equipment and qualified personnel were reported in hospitals and diagnostic laboratories. When a crisis is global, supply chains are strained worldwide and external help may not be readily available. In Switzerland, as part of the efforts of the Swiss National COVID-19 Science Task Force, we developed a tailor-made web-based tool where needs and offers for critical laboratory equipment and expertise can be brought together, coordinated, prioritized and validated. This Academic Resources for COVID-19 (ARC) Platform presents the specialized needs of diagnostic laboratories to academic research groups at universities, allowing the sourcing of said needs from unconventional supply channels, while keeping the entities tasked with coordination of the crisis response in control of each part of the process. An instance of the ARC Platform is operated in Switzerland (arc.epfl.ch) catering to the diagnostic efforts in Switzerland and sourcing from the Swiss academic sector. The underlying technology has been released as open source so that others can adopt the customizable web-platform for need/supply match-making in their own relief efforts, during the COVID-19 pandemic or any future disaster.